Comparison of the difference between income quintiles with the slope index of inequality. (13th November 2019) - Khang, Y H; Lim, D; Bahk, J; Kim, I; Kang, H Y; Chang, Y; Jung-Choi, K
Abstract: Background: The difference between income quintiles in health is relatively well accepted by the general public as a measure of health inequality. However, the slope index of inequality (SII) in health reflects the patterns of all social groups, including the middle 60%, and it could therefore be considered more academically desirable. If these two measures are closely correlated, the widespread use of the difference between income quintiles in health would be better supported. This study was conducted to compare differences between income quintiles in life expectancy (LE) and healthy life expectancy (HLE) with the SII. Methods: Data on LE and HLE by income quintile from all 252 subnational districts of Korea were obtained using the National Health Information Database of the National Health Insurance Service and the Korea Community Health Survey. The SII was estimated with linear regression analysis, and Pearson correlation coefficients between differences between income quintiles and the SII were computed. Results: The correlation coefficients between differences between income quintiles and the SII were generally high: 0.97 (95% CI: 0.96-0.98) for LE in men and women combined and 0.96 (95% CI: 0.94-0.97) for HLE in men and women combined. In most districts, the SII was greater than the difference between income quintiles. Conclusions: Differences between income quintiles were closely correlated with the SII. The widespread use of differences between income quintiles in health as a measure of health inequality may be preferable for communicating results of health inequality measurements to the public. Key messages: Differences in life expectancy and health life expectancy between income quintiles were closely correlated with the slope index of inequality in life expectancy and healthy life expectancy. The widespread use of differences between income quintiles in health as a measure of health inequality may be preferable for communicating results of health inequality measurements to the public.